Dynamics of Wellbeing On Emerging Adolescence Fatherless InMTs Darul Ulum Palangka Raya - Aishah, Fhitri; Hamdanah; Surawan (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2024)
The role of the father in the family has an important role, social construction in society shapes the role of the father as afigure who is the head of the household, provides for and is arole model for his children. This study explores the dynamicsof well-being in adolescents who lose a father figure in thetransition to adulthood. Focusing on fatherless adolescents, the research was conducted in the environment of MTs DarulUlum Palangka Raya using descriptive qualitative methodswith 14 subjects. Data were collected through observation, interviews, and documentation, then analyzed to understandthe factors that influence the wellbeing of fatherlessadolescents. The results showed that fatherless children tendto experience difficulties in emotion regulation, socialinteraction, self-esteem, decision making, and managingstress. The lack of a father figure negatively impacts theiremotional development. It is important to deeply understandthe dynamics of fatherless adolescents' well-being in order toprovide appropriate support for their development. Propermentoring, understanding, and support from the closestenvironment, especially parents, play a major role in helpingfatherless adolescents manage emotions, make decisions, andimprove their emotional well-being. The implications of thisstudy suggest the need for public awareness, inclusiveeducation programs, and psychological support for fatherlessadolescents to optimize their well-being holistically.